Teologi Tentang Berpacaran Menurut Amsal 30:18-19 - Saragih, Eliyansen (BIA, 2018)
Dating is an irresistible phenomenon in today's youth life. Actually, dating is a way that brings youth in two directions, towards a good or bad life. Therefore all parties in the community must be wise to anticipate. Proverbs 30: 18-19 can be a theological basis for the phenomenon of dating. Interestingly, numerical poetry in this text can give direction about relationships between young men and women. In this text, we can see that poems direct all audiences through observing the movements of objects in nature, can observe the essence of the formation of relations between men and women. Practically, this text can be applied to equip young people in anticipating the phenomenon of dating. Every young couple who is committed to dating must be equipped with this theological basis, so that their lives can be constantly built physically, mentally and spiritually. To apply the text of the Proverbs 30: 18-19 is an attempt to answer it.Abstrak: Bepacaran adalah fenomena yang tak tertahankan dalam kehidupan remaja saat ini. Berpacaran adalah cara yang membawa kehidupan remaja ke dua arah, menuju kehidupan yang baik atau buruk. Semua pihak dalam masyarakat harus bijak mengantisipasinya. Amsal 30:18-19 dapat menjadi dasar teologis untuk fenomena berpacaran. Menariknya, sejumlah puisi dalam teks ini memberikan arahan tentang hubungan antara pria dan wanita. Dalam teks ini dapat dilihat bahwa penyair mengarahkan pembaca dengan mengamati pergerakan benda-benda di alam yang dapat menjadi dasar dari pembentukan hubungan antara pria dan wanita. Secara praktis, teks ini dapat diterapkan untuk memperlengkapi kaum muda dalam mengantisipasi fenomena berpacaran. Setiap pasangan remaja yang berkomitmen untuk berpacaran harus dilengkapi dengan dasar teologis ini, sehingga kehidupan mereka dapat terus dibangun secara fisik, mental dan spiritual. Menerapkan teks Amsal 30:18-19 merupakan upaya untuk menjawabnya.